Metode Storytelling Islami Untuk Meningkatkan Kecerdasan Emosional Anak Usia Dini - Syukron, Ahmad; Yudha, Rivo Panji (Generasi Emas, 2025)
This research aims to explore the effectiveness of Islamic storytelling methods in enhancing the emotional intelligence of early childhood children, particularly those aged 5-6 years at TKIT Al-Adzkiyah Bekasi. Utilizing a quasi-experimental design, this study involves two groups: the experimental group receiving the Islamic storytelling intervention and the control group following the regular curriculum. The intervention is conducted over 8 weeks with storytelling sessions lasting 30 minutes, three times a week. Data is collected through the Child Emotional Intelligence Scale (SKEA) and analyzed using paired t-tests and thematic analysis for qualitative data. The research findings indicate that although there is no statistically significant difference between the experimental and control groups (p = 0.938), the Islamic storytelling method still has the potential to serve as an effective educational tool in developing children's emotional intelligence. This study emphasizes the importance of developing better methodologies, implementations, and outcome measurements to enhance the effectiveness of interventions. Recommendations for future research include extending the duration of interventions, increasing the sample size, and involving parents in the storytelling process. Thus, this research makes an important contribution to the development of Islamic-based educational methods that focus not only on emotional intelligence but also on character formation in children.